1998
DOI: 10.1002/(sici)1097-4628(19980705)69:1<201::aid-app23>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

The nature and location of SEBS-MA compatibilizer in polyethylene-wood flour composites

Abstract: ABSTRACT:A maleic-anhydride-grafted styrene-ethylene-butylene-styrene (SEBS-MA) triblock copolymer has been used as a compatibilizer in low-density polyethylenewood flour (LDPE-WF) composite system. The location of compatibilizer was studied using transmission electron microscopy (TEM). The unsaturated parts of the copolymer were stained with osmium tetraoxide (OsO 4 ) to enhance contrast between the different phases. TEM micrographs indicated that part of the compatibilizer was located at the interface betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(46 citation statements)
references
References 5 publications
1
41
0
1
Order By: Relevance
“…A marked increase of the modulu,s up to about 1,750 MPa, was found for PS/Cell (60/40) upon addition of PS-co-MA (16 pph), while the strength at max and elongation at break decreased, depending on the fiber/compatibilizer ratio (Figure 14). Otherwise, the addition of SEBS-g-MA copolymer caused a ductile behavior with lower modulus and increased elongation at break, owing to the ethylene-butene elastomeric block in the copolymer chain [28]. However, as it was pointed out by SEM analysis of fracture surfaces of binary SEBS-g-MA/Cell samples, a stronger surface adhesion accompanied by extended fiber fraying was noticed with respect to PS-co-MA/Cell samples.…”
Section: Composites With Ps Matrixmentioning
confidence: 89%
“…A marked increase of the modulu,s up to about 1,750 MPa, was found for PS/Cell (60/40) upon addition of PS-co-MA (16 pph), while the strength at max and elongation at break decreased, depending on the fiber/compatibilizer ratio (Figure 14). Otherwise, the addition of SEBS-g-MA copolymer caused a ductile behavior with lower modulus and increased elongation at break, owing to the ethylene-butene elastomeric block in the copolymer chain [28]. However, as it was pointed out by SEM analysis of fracture surfaces of binary SEBS-g-MA/Cell samples, a stronger surface adhesion accompanied by extended fiber fraying was noticed with respect to PS-co-MA/Cell samples.…”
Section: Composites With Ps Matrixmentioning
confidence: 89%
“…Different coupling agents have been used to modify the polymeric matrix and improve the interfacial strength and subsequently the mechanical properties of the products. Maleic anhydride grafted styrene-ethylene-butylene-styrene (SEBS-g-MA) ( Oksman et al, 1998) and maleic anhydride grafted polyolefin such as HDPE-g-MA (Polec et al, 2010), PP-g-MA (Farsi, 2010), and LDPE-g-MA (Tasdemir et al, 2009) are the most common examples of reported works in the literature.…”
mentioning
confidence: 99%
“…Therefore, it is a new type of biodegradable 3D printing filament with broad prospects for further development. However, it is noted that although wood flour and PLA can be mixed evenly and wood flour can be covered by polylactic acid molecules, the interfacial compatibility and tenacity of the composite materials are not satisfactory (Oksman et al 1998;Lai et al 2003). Moreover, the addition of wood flour can limit the movement of the macromolecular chain of PLA and reduce the stereo-tacticity of PLA, which leads to a significant reduction in the crystallization ability of PLA (Liu et al 2013).…”
Section: Introductionmentioning
confidence: 99%